The Sustainable Environmental Protection Deregulation Concept During the Covid-19 Pandemic - Imamulhadi Imamulhadi (Faculty of Law, Universitas Padjadjaran, 2021)
The economic recession due to the Covid-19 pandemic has forced several countries to deregulate environmental protection. In response to such policy, many environmental activists and environmentalists worry that deregulation will cause a negative impact on the mitigation of climate change’s effects. Therefore, it is necessary to examine whether or not the deregulation of environmental protection in Indonesia is in line with the objectives of sustainable development. The provisions of the deregulation of environmental protection in Indonesia aims to encourage and accelerate investment through the simplification of licensing procedures, eradicating corruption in the licensing sector, increasing economic growth and gross domestic product, encouraging equitable development, and providing employment opportunities. This study concludes that Indonesia’s deregulation policy does not violate the minimum tolerance standard of environmental protection. It also does not eliminate the precautionary principle and environmental impact analysis as a preventive measure. In addition, it does not revoke environmental quality standards and damage quality standards as monitoring, control, and enforcement instruments. The deregulation accordingly still adheres to the three pillars of sustainable development.DOI: https://doi.org/10.22304/pjih.v8n3.a4